2004
DOI: 10.1093/toxsci/kfh119
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-Substituted PCBs Kill Cells by Altering Membrane Structure

Abstract: Our previous studies have demonstrated that ortho-substituted PCBs cause a rapid cell death in both thymocytes and cerebellar granule cell neurons, whereas coplanar congeners are without effect at comparable concentrations and exposure times. We have demonstrated that multiple membrane components are altered by these exposures, including the plasma membrane, mitochondria, and endoplasmic reticulum. The present experiments were designed to test the hypothesis that because of their stereochemistry, ortho-substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 43 publications
(48 reference statements)
4
48
0
Order By: Relevance
“…It has been demonstrated that ortho-substituted PCB congeners (but not coplanar congeners) alter calcium homeostasis by inducing changes in the integrity of mitochondrial and ER membranes which is accompanied by a decrease in mitochondrial membrane potential and accumulation of intracellular calcium [58]. It has also been shown that PCB 47 and PCB 52 (non-coplanar congeners; 10 lM) significantly compromised plasma membrane integrity concomitant with an accumulation of intracellular calcium [59]. Disruption of membrane structure, whether it is the plasma membrane or those of intracellular organelles, can cause changes in ion permeabilities through voltage or ligand gated channels as well as changes in activity of membrane bound enzymes [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that ortho-substituted PCB congeners (but not coplanar congeners) alter calcium homeostasis by inducing changes in the integrity of mitochondrial and ER membranes which is accompanied by a decrease in mitochondrial membrane potential and accumulation of intracellular calcium [58]. It has also been shown that PCB 47 and PCB 52 (non-coplanar congeners; 10 lM) significantly compromised plasma membrane integrity concomitant with an accumulation of intracellular calcium [59]. Disruption of membrane structure, whether it is the plasma membrane or those of intracellular organelles, can cause changes in ion permeabilities through voltage or ligand gated channels as well as changes in activity of membrane bound enzymes [59].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that PCB 47 and PCB 52 (non-coplanar congeners; 10 lM) significantly compromised plasma membrane integrity concomitant with an accumulation of intracellular calcium [59]. Disruption of membrane structure, whether it is the plasma membrane or those of intracellular organelles, can cause changes in ion permeabilities through voltage or ligand gated channels as well as changes in activity of membrane bound enzymes [59]. These nonspecific effects could certainly contribute to loss of calcium sequestration as presented in the current report.…”
Section: Discussionmentioning
confidence: 99%
“…Some environmental contaminants, such as orthosubstituted polychlorinated biphenyls (PCBs), cause an increase in membrane fluidity in neurons and thymocytes but also cause a rapid cell death in isolated cell systems [12]. Toxaphene, a chlorinated pesticide, decreases membrane fluidity and also causes acute cell death in thymocytes [13].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on the potential toxicity of substituted BPs in vivo [2,17,18] but very little work has been carried out on the evaluation of the molecular characteristics responsible for their toxicity and the mechanism of their interaction at a cellular and plasma membrane level. According to some studies, non-planar o-substituted BPs increased the cell membrane leakiness and decreased the membrane integrity compared to the planar BPs [17][18][19]. While other studies have shown the non-planar o-substituted molecules to be less active compared to the planar p-substituted molecules because of the steric hindrance of the osubstituted species which influences their penetration into the phospholipid membrane [20][21][22].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%